2015
DOI: 10.3109/02813432.2015.1114348
|View full text |Cite
|
Sign up to set email alerts
|

What a difference a CRP makes. A prospective observational study on how point-of-care C-reactive protein testing influences antibiotic prescription for respiratory tract infections in Swedish primary health care

Abstract: Objective: To explore how C-reactive protein (CRP) tests serve to support physicians in decisions concerning antibiotic prescription to patients with respiratory tract infections (RTI). Design. Prospective observational study. Setting: Primary health care centres in western Sweden. Subjects. Physicians in primary health care. Patients with acute RTI. Main outcome measures: Physician willingness to measure CRP, their ability to estimate CRP, and changes in decision-making concerning antibiotic treatment based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…Use of CRP is known to be frequent in the assessment of respiratory infections in Scandinavia, but it is not recommended in the initial judgment of pneumonia in primary care. 6,12,15 In the present study, CRP testing increased and the frequency was high (71.4%) compared to a 2009 Swedish study by Engström et al, in which the corresponding frequency was only 38% in pneumonia diagnosis, and another 2016 study by Tyrstrup et al in which the testing rate was 60.4%, indicating that usage of point of care CRP has progressively increased. 16,17 Earlier studies have shown that assessment of pneumonia differs between countries.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 50%
“…Use of CRP is known to be frequent in the assessment of respiratory infections in Scandinavia, but it is not recommended in the initial judgment of pneumonia in primary care. 6,12,15 In the present study, CRP testing increased and the frequency was high (71.4%) compared to a 2009 Swedish study by Engström et al, in which the corresponding frequency was only 38% in pneumonia diagnosis, and another 2016 study by Tyrstrup et al in which the testing rate was 60.4%, indicating that usage of point of care CRP has progressively increased. 16,17 Earlier studies have shown that assessment of pneumonia differs between countries.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 50%
“… 26 Another recently published Swedish study where both children and adults were included found CRP testing in 38% and that CRP pretesting correlated with increased antibiotic prescription. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies on POC CRP testing were excluded at full-text screening because they were not in an ambulatory care setting,26 27 no comparator group without POC CRP testing was present,28–31 the effect of the POC CRP could not be assessed separately or did not guide treatment decisions,32–34 the focus was cost-effectiveness modelling35–37 or decision-making analysis,38 39 or it was not a clinical trial (study protocol or response to systematic review)40 41 (online supplementary file 3).…”
Section: Resultsmentioning
confidence: 99%